(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
The article analyzes the distribution of endocrine diseases. The main cause of endocrine disease, or pathology of the thyroid gland, arises from the development of a lack of conditions associated with a little intake of iodine from the external environment. The growth in development and the increase in registrations of these diseases has led to a much larger spread of the number of people with disabilities. Before medicine is faced with an important task of carrying out sanitary preventive measures, organizing a medical examination among the population, covering timely laboratory examination for early diagnosis of patients with endemic goiter and treatment before the transition to a chronic form to prevent disability.